Kelp helps - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Is the sea near your farm? Why not embark on sea farming or as the cultivation of seaweeds is called mariculture. The virtues of seaweeds have been known for ages but only in the past few decades have both production and consumption started to...